2019
DOI: 10.1101/853317
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Distinct Neural Signatures of Outcome Monitoring following Selection and Execution Errors

Abstract: 1Losing a point playing tennis may result from poor shot selection or poor stroke execution. To 2 explore how the brain responds to these different types of errors, we examined EEG 3 signatures of feedback-related processing while participants performed a simple decision-4 making task. In Experiment 1, we used a task in which unrewarded outcomes were framed as 5 selection errors, similar to how feedback information is treated in most studies. Consistent 6 with previous work, EEG differences between rewarded an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 87 publications
(139 reference statements)
1
4
0
Order By: Relevance
“…For example, when throwing a ball to a specific target, the wrong target could have been chosen, but missing the target could also be induced by a wrong release point, a wrong estimation of the ball's flight curve, the distance to the target area, the control of the muscular system, the wrong standing position, a slippery surface, etc. It has been shown that feedback focusing on execution errors induces higher FRN amplitudes compared to feedback that is related to selection errors (Mushtaq et al, 2022). This supports the present finding that the FRN amplitude was higher in motor tasks, where feedback is related to movement execution (and action selection) than in cognitive tasks, where feedback is related exclusively to action selection.…”
Section: Discussion Frn Amplitudesupporting
confidence: 91%
See 4 more Smart Citations
“…For example, when throwing a ball to a specific target, the wrong target could have been chosen, but missing the target could also be induced by a wrong release point, a wrong estimation of the ball's flight curve, the distance to the target area, the control of the muscular system, the wrong standing position, a slippery surface, etc. It has been shown that feedback focusing on execution errors induces higher FRN amplitudes compared to feedback that is related to selection errors (Mushtaq et al, 2022). This supports the present finding that the FRN amplitude was higher in motor tasks, where feedback is related to movement execution (and action selection) than in cognitive tasks, where feedback is related exclusively to action selection.…”
Section: Discussion Frn Amplitudesupporting
confidence: 91%
“…Errors in cognitive tasks are commonly assigned to action selection for highly automatized (and simple) button presses. In contrast, errors in motor tasks can arise for different task elements during action selection, as well as during movement execution (De Bruijn et al, 2003;Maurer et al, 2021;Mushtaq et al, 2022). For example, when throwing a ball to a specific target, the wrong target could have been chosen, but missing the target could also be induced by a wrong release point, a wrong estimation of the ball's flight curve, the distance to the target area, the control of the muscular system, the wrong standing position, a slippery surface, etc.…”
Section: Discussion Frn Amplitudementioning
confidence: 99%
See 3 more Smart Citations